Evolutionary approach to lifecycle management of knowledge-intensive business processes - Чала, О. В. (Science-based technologies, 2017)
The article proposes an approach to lifecycle management of knowledge-intensive business processes, combining cascade and evolutionary strategy for building business processes with the level of maturity of these processes. This approach is based on the principles of evolutionary life cycle management of knowledge-intensive business processes. The principle of evolutionary life cycle management of knowledge-intensive business processes is a combination of focused improvement of the process by supplementing his knowledge in the performance context-oriented rules and restrictions startup sequence actions resulting from externalization personal knowledge and experience that have been used performers at process management and reengineering of the process in case of failure to reach at advanced process defined performance indicators. This makes it possible to form a methodological framework for automating continuous improvement of knowledge-intensive business processes by including externalized model of knowledge performers and redesign of processes in a fundamental change priori defined requirements.